2019
DOI: 10.1111/1744-9987.12792
|View full text |Cite
|
Sign up to set email alerts
|

NMR‐based lipoprotein analysis for patients with severe hypercholesterolemia undergoing lipoprotein apheresis or PCSK9‐inhibitor therapy (NAPALI‐Study)

Abstract: Taking into account the discordance between low‐density lipoprotein cholesterol (LDL‐C) and LDL particle (LDL‐P) number, cardiovascular risk more closely correlates with LDL‐P in patients. The aim of our study was to evaluate the number of lipid particles in patients with severe hypercholesterolemia treated with different lipid‐lowering regimens. Four groups of patients differing with respect to lipid‐lowering therapy were recruited from hypercholesterolemic outpatients and lipoprotein apheresis (LA) facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The present study confirmed that patients at high cardiovascular risk treated for four weeks with PCSK9-I displayed a major decrease in the levels of total cholesterol and atherogenic lipids, including LDL-C and non-HDL-C, as well as apoB. A moderate but significant increase in HDL-C and apoA-I was also observed, which is an effect of PCSK9-I that has been previously reported in a number of clinical trials, albeit with some discrepancies [14,15,[28][29][30][31][32]. Although the level of HDL-C has been repeatedly inversely related to cardiovascular risk in epidemiological studies, a single measurement of HDL-C does not necessarily reflect the functionality of HDL particles and their pleiotropic atheroprotective properties.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study confirmed that patients at high cardiovascular risk treated for four weeks with PCSK9-I displayed a major decrease in the levels of total cholesterol and atherogenic lipids, including LDL-C and non-HDL-C, as well as apoB. A moderate but significant increase in HDL-C and apoA-I was also observed, which is an effect of PCSK9-I that has been previously reported in a number of clinical trials, albeit with some discrepancies [14,15,[28][29][30][31][32]. Although the level of HDL-C has been repeatedly inversely related to cardiovascular risk in epidemiological studies, a single measurement of HDL-C does not necessarily reflect the functionality of HDL particles and their pleiotropic atheroprotective properties.…”
Section: Discussionsupporting
confidence: 90%
“…To date, only four studies have analyzed the effects of PCSK9-I therapy on HDL particle profiles measured by NMR, with one study reporting no change [14], while the others found a moderate increase Journal Pre-proof in the total HDL-P level of approximately 10% [15][16][17]. However, the aforementioned studies were performed in patients from randomized controlled trials and were mostly restricted to analysis of the total HDL-P concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Also, no classification for HDL subclasses analysed by NMR has been yet approved for routine purpose. For instance, the analytical method developed by LipoScience (now LabCorp, Raleigh, NC) grouped HDL particles into 3 subclasses from small (S-HDL-P, 7.3-8.2 nm), medium (M-HDL-P, 8.2-9.4 nm) to large (L-HDL-P, 9.4-14 nm) with small and medium-sized HDL particles being sometimes grouped (MS-HDL-P, 7.3-9.4 nm), while the AXINON lipoFIT-S100 system (Numares AG, Regensburg, Germany) used in the present study grouped HDL subclasses into small (SHDL-P, 7.3-8.7 nm) and large (LHDL-P, 8.8-13 nm) 11,12 . In this latest classification, it is worth mentioning that the estimated diameter ranges for SHDL-P and LHDL-P were similar to those for HDL 3c+3b+3a (7.2-7.8 nm; 7.8-8.2 nm; 8.2-8.8 nm) and HDL 2a+2b (8.8-9.7 nm; 9.7-12.9 nm), respectively, as isolated from plasma by density gradient ultracentrifugation and analyzed by electrophoresis on a nondenaturing gel 13,14 .…”
Section: Discussionmentioning
confidence: 77%
“…HDL measurement by nuclear Magnetic Resonance (nMR) spectroscopy. HDL particle concentration and size were measured by NMR spectroscopy using the AXINON lipoFIT-S100 test system (Numares AG, Regensburg, Germany) as previously described 11,12,23 . Serum samples for NMR spectroscopy were stored at −80 °C and kept unthawed until the day of NMR measurements.…”
Section: Assessment Of Cad Severity and Extension And Estimation Of Cmentioning
confidence: 99%
“…Although mass spectrometry-based approaches can resolve a higher number of metabolites than NMR spectroscopy, clear advantages of the NMR technique include the non-destructive character of the analysis, simple sample processing and high analytical reproducibility. A standardized NMR platform was shown to be a powerful analytical tool for an in-depth lipoprotein analysis in various contexts [ 9 , 10 , 11 , 12 , 13 ]. Recently, a metabolomic analysis using the same technology and AI-based approaches allowed the identification of constellations of urinary and blood metabolites as novel biomarkers for a non-invasive assessment of a renal allograft rejection [ 14 , 15 ] and the precise estimation of a kidney function [ 16 ], respectively.…”
Section: Introductionmentioning
confidence: 99%